Morphological Stylistic Analysis found in Langston Hughes’s Poem “Harlem” - Zahara, Ayuna; Hidayat, Chatrine Aulia; Rangkuti, Rahmadsyah (Linguistics and ELT Journal, 2023)
This study conducts a morphological stylistic analysis of Langston Hughes's renowned poem "Harlem" with the overarching objective of identifying and categorizing the types of morphemes employed within the poem.  Moreover, this research seeks to determine the most dominant type of morpheme in the poem. The researchers used descriptive qualitative method in analyzing the data. Employing qualitative methods, the analysis focuses on identifying various morpheme types of free morpheme and bound morpheme, such as lexical, functional, derivational, inflectional morphemes. Through a line-by-line examination, the study scrutinizes the presence and role of morphemes in constructing the vivid and evocative imagery characteristic of "Harlem." In the result, the researchers found 16 lexical morphemes (nouns, verbs, adjectives, adverbs) 25 functional morphemes (pronouns, prepositions, articles, conjunctions), 7 inflectional and 3 derivational suffixes. Furthermore, the results of the analysis shows that the most dominant types of morphemes are functional morpheme.